Physicochemical and Protein Quality of Noodles Made with Wheat and Okara Flour Blends - Okpala, L.C.; Egbadon, L.; Okoye, S. (Pakistan Journal of Nutrition, 2016)
Wheat flour was substituted with okara flour in order to obtain noodles with acceptable physicochemical, protein and sensory quality. Seven substitution levels were tested: 5, 16.25, 20, 27, 35, 38.75 and 50%. As the level of okara flour increased in the blends, the levels of protein, ash, fat and fibre contents of the noodles increased. Increased levels of okara however decreased cooking time but increased cooking losses. The total essential amino acids of noodles from the blends ranged from 26.07-40.37 g/100 g crude protein with histidine or from 43.38-46.49% of the total amino acids. Glutamic acid was the most abundant amino acid in the samples while leucine was the most abundant essential amino acid (5.52-7.86 g/100 g crude protein). Methionine was the limiting amino acid (0.80-1.38 g/100 g crude protein). The predicted protein efficiency ratio, biological value and essential amino acid index of the samples ranged from 1.81-2.88, 53.05-88.8 and 59.4-92.2%, respectively. Sensory evaluation revealed that noodles made with 5% okara and 95% wheat flour was the best in terms of all the attributes studied and was even better than the control (100% wheat). The study has shown that the utilization of okara flour will go a long way in not only increasing utilization of waste but will also encourage the development of variety and value added noodles.